CONGESTION PRICING IN SELECTED CITIES IN SOUTHEAST ASIA - Tan Eng Hwa; Meenchee Hong; Ei Yet Chu (Journal of Islamic, Social, Economics and Development, 2022)
The aim the conceptual paper is to improve the level of the road traffic congestion in selected cities of Southeast Asia through implementation of congestion pricing. Traffic congestion is a common phenomenon in most cities in Southeast Asia. It is a significant impediment to the achievement of economic goals. Many remedies have been put forward to ease road congestion, some of which is congestion price. Economists and transportation experts’ views congestion pricing as the most efficient means to mitigate traffic congestion because it employs price mechanism. Many research deals with congestion price, and what amount to be imposed. However, results from these previous studies were not enough to validate what should be the components of a congestion price that will regulate and efficiently allocate the resources. Thus, this conceptual paper suggests to estimate and determine the congestion pricing to be imposed in the selected cities in Southeast Asia based on the value of time of travellers. It also proposes to further evaluates the effect of congestion pricing on transport infrastructure investment on the road and in railway. The outcome of the study may act as guidelines for government agencies and transportation authority in developing policies and strategies to enhance the efficiency of public infrastructure and reduce traffic congestion.